Adaptation in contemporary theatre performing literature - Babbage, Frances (London, UK Methuen Drama, trademark of Bloomsbury Publishing Plc, 2019)
"Why are so many theatre productions adaptations of one kind of another? Why do contemporary practitioners turn so frequently to non-dramatic texts for inspiration? This study explores the fascination of novels, short stories, children's books and autobiographies for theatre makers and examines what 'becomes' of literary texts when these are filtered into contemporary practice that includes physical theatre, multimedia performance, puppetry, immersive and site-specific performance and live art. In Adaptation in Contemporary Theatre, Frances Babbage sets out a series of fresh critical perspectives on the theory of adaptation in theatre-making, focusing on meditations of prose literature within contemporary performance. Individual chapters explore the significance and impact of books as physical objects within productions; the relationship between the dramatic adaptation and literary edition; storytelling on the page and in performance; literary space and theatrical space; and prose fiction reframed as 'found text' in contemporary theatre and live art. Case studies are drawn from internationally acclaimed companies including Complicite, Elevator Repair Service, Kneehigh, Forced Entertainment, Gob Squad, Teatro Kismet and Stan's Cafe. Adaptation in Contemporary Theatre is a compelling and provocative resource for anyone interested in the potential and the challenges of using prose literature ad material for new theatrical performance. "--Provided by publisher.
Chapter 1 Adaptation and the Theatre -- Chapter 2 Performing Books -- Chapter 3 Story: Adaptation and the Act of Telling -- Chapter 4 Layered Space: Adaptation, Immersion and Site -- Chapter 5 Resisting Adaptation.
Includes bibliographical references and index.
Keywords: Literature -- Adaptations -- History and criticism; Drama -- Adaptations -- History and criticism; Stage adaptations -- History and criticism; Theater -- Production and direction; Playwriting